COMPARISON BETWEEN THE ROLES OF THE MEDICAL AND NURSING COMMITTES IN THE MARKETING SYSTEM TO IMPROVE THE REGIONAL GENERAL HOSPITAL PERFORMANCE OF MUNA REGENCY, SOUTHEAST SULAWESI PROVINCE: Role of medical and nursing committees - La Ode Kamalia (STIKes Mandala Waluya Kendari, 2022)
Background: Based on the Health Profile from 2012 to 2019, the performance of Regional General Hospitals in Indonesia, especially in Muna Regency, Southeast Sulawesi Province as measured by the Bed Occupancy Rate (BOR)is below 60%. Similarly, the marketing implementation is relatively weak, while the roles and functions of the medical and nursing committees in accordance with Law No. 44 of 2009 concerning Hospitals, are also not optimal. Therefore, this study aims to develop and examine the role of professional committees (medical and nursing) in the marketing system to improve hospital performance. Methods: This study was conducted using a pre-experimental design, namely pre-test before treatment, and further post-test on 30 respondents. The population was 32 members of the Professional Committee (Medical and Nursing) determined using the Yamane Slovin Uma Sekaran formula (2013) and probability sampling technique. Furthermore, SEM (Structural Equation Modeling) analysis was used based on Partial Least Square (PLS) variance to determine the magnitude of the Medical and Nursing Committees' roles. A t-test was also performed to assess the difference between the roles of these Committees in the marketing system to improve hospital performance before and after the intervention. Result: Theinferential statistical analysis proved that the medical and nursing committees play significant roleswhichdirectlyaffect the marketing system (orientation and marketing strategy) andimprove hospital performance. Conclusion: Based on the results, the medical and nursing committees play an important role in improving the marketing system and hospital performance. Therefore, it is recommended that the local governments through the Director of Regional General Hospitals empower these. committees to play a role in the marketing system and improve the hospital performance in the future.